Creating Social Sustainability Through Distributing Leadership and Co-Responsibility in Corporate Volunteering. (April 2023) - Hatami, Akram; Hermes, Jan; Keränen, Anne; Ulkuniemi, Pauliina
In this article, we apply a distributed perspective on leadership to the study of co-responsibility and social sustainability in corporate volunteering. An approach to leadership as a distributed and collective phenomenon, in which leadership is shared, is highlighted as a method of developing a more responsible and people-focused approach to sustainability. Co-responsibility highlights the transition from individual to co-created responsibility, influenced by different actors and offering a wider approach to responsibility. The present qualitative study employs two corporate volunteering cases from Finland as an empirical context for distributing leadership. As a result, the study suggests three transitions in organizational life and leadership, including transition in values, organizing, and dynamism. The study contributes to the discussion of social sustainability by demonstrating how several transitions in terms of leadership are necessary to enable an emerging sense of co-responsibility in companies which is argued as the key to companies' social sustainability.